PENERAPAN PENDEKATAN KONSTRUKTIVISME SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN INTERPRETATIF BAGI SISWA - Fimeir Liadi; Abu Darim; Tri Warjuningsing (Transformatif, 2018)
Reading is an important language skill for students. Through reading, students are able to get  lots  of  information from various  reading sources. However, after observation and interview  are  conducted, it shows that the ability of interpretative  reading comprehension for the students still needs to be improved. Therefore,  the  researcher thinks that the improvement of the students’ ability in interpretative reading comprehension can be done by using constructivism approach.In relation with the effort to improve the ability in interpretative reading comprehension, the specific problem limitation studied is as follow. How far is the implementation of constructivism approach in pre reading stage, while reading stage, and post reading stage can improve the ability of interpretative reading comprehension for the students of the grade? In accordance with it, the specific objective of this research is to describe the implementation of constructivism approach in pre reading stage, while reading stage, and post reading stage.Keywords: Constructivism  approach, interpretative reading comprehension